ANALISIS EFEKTIVITAS SISTEM DAN PROSEDUR AKUNTANSI BELANJA KEMENTERIAN PUPR (ETNOMETODOLOGI SATUAN KERJA NON VERTIKALTERTENTU PENGEMBANGAN, PENGENDALIAN, PELAKSANAAN PEKERJAAN STRATEGIS BIDANG PU DANPR LAINNYA) - Inge Damayanti, - (2019)
This research aims to know the effectiveness of the system and procedures cost accounting in the Development, Control, Execution of the Strategic Areas of Non Specific Vertical Work Unit of Ministry of PUPR and identify constraints in the attainment of the realization of the SPM and SP2D through the planning process, implementation up to reporting as an assessment of the achievement of an activity or program that has been planned. This research used the qualitative research paradigm of the interpretive methods with etnometodology approach. Data analysis techniques used at the time of data collection in the form of observation, interview and documentation to the key informant and the informant's supporters and by collecting documents as supporting data research. The results of this study showed that the effectiveness of the system and procedure cost accounting are in accordance with the Government Rule No. 71 Year 2010 on Government accounting standards and the results of the evaluation-related constraints in the effectiveness of the system and procedure cost accounting in the Development, Control, Execution of the Strategic Areas of Non Specific Vertical Work Unit.